Correlation Between Mother's Age, Chronic Energy Deficiency (KEK) and Anemia to Low Birth Weight Babies at Purwodadi II Public Health Center - Yuwanti; Mahanani Mulyaningrum; Nurulistyawan Tri Purnanto (Jurnal Profesi Bidan Indonesia, 2022)
Background: Low birth weight (BBLR) is a condition where the baby born has a birth weight of < 2500 grams. Low birth weight is caused by various conditions such as less than a month of pregnancy, maternal age, chronic lack of energy conditions (KEK), maternal diseases, anemia, drug use and economic conditions. Objective: This study aims to determine the relationship between maternal age, anemia, and Chronic Lack of Energy (KEK) to low birth weight. Method: This type of research is analytical research. The study sample was 45 people. Test analytics using Chi Square Test. Result: Conclusion: maternal age, anemia and chronic energy deficiency are not associated with the incidence of Low Birth Weight (BBLR). Background